Biosynthesis of CuO nanoparticles using aqueous extract of herbal tea (Stachys Lavandulifolia) flowers and evaluation of its catalytic activity - Hojat Veisi (Nature Portfolio, 2021)
Abstract Plant derived biogenic synthesis of nanoparticles (NP) has been the recent trend in material science as featured sustainable catalysts. A great deal of the current nanocatalytic research has been oriented on the bio-inspired green catalysts based on their wide applicability. In this context, CuO NPs are synthesized following a green approach using an herbal tea (Stachys Lavandulifolia) flower extract. The phytochemicals contained in it were used asthe internal reductant without applying harsh chemicals or strong heat. The derived nanoparticles also got stabilized by the biomolecular capping. The as-synthesized CuO NPs was characterized over FT-IR, FE-SEM, EDS, TEM, XRD, TGA and UV–Vis spectroscopy. These NPs were exploited as a competent catalyst in the aryl and heteroaryl C–heteroatom (N, O, S) cross coupling reactions affording outstanding yields. The nanocatalyst was isolated and recycled in 8 consecutive runs with reproducible catalytic activity. Rigidity of the CuO/S. Lavandulifolia nanocomposite was further justified by leaching test and heterogeneity test.